Effect of mixed surfactants on stratum corneum: a drying stress and Raman spectroscopy study. (12th June 2014) - Purohit, P.; Chandar, P.; Vilinska, A.; Ananthapadmanabhan, K. P.; Somasundaran, P.
Synopsis Objective Stratum corneum (SC) lipids are known to play an important role in barrier properties of skin by maintaining the optimal hydration levels. The disruption of SC lipids by cleanser surfactants is believed to lead to dry skin damage which can be a precursor to other skin disorders. The purpose of this study is to investigate the effects of commonly used anionic and zwitterionic surfactants sodium lauryl ether sulphate (SLES) and cocoamidopropyl betaine (CAPB) on the generation of drying stresses in SC and the role played by lipids. Methods Stratum corneum separated from pig skin was treated with various surfactants (SDS, SLES and CAPB) their mixtures and solvents. The tensile response to these treatments was measured by using a dynamic mechanical thermal analyzer. A Raman spectroscopy study of the treated samples was performed to investigate the effects of lipid modification (lipid chain conformational order and lipid removal) on stress generation in SC. Results The effects of commonly used anionic and zwitterionic surfactants on the generation of drying stresses in SC were studied. Although known to be milder in comparison with SDS, both SLES and CAPB generated high drying stresses individually. In mixtures, SLES–CAPB at 4 : 1 ratio leads to lower drying stress as compared to water alone. A Raman spectroscopic study of surfactant‐treated SC shows changes in lipid chain conformational order as well as a decrease in lipid–protein ratio in SC. A chloroform–methanol 2 : 1 treatment leads to the highest drying stress as well delipidization of SC. Conclusion The results show a correlation between generation of drying stress in SC and extent of lipid modification. We propose that the changes in lipid conformational order and removal of lipid components affect the stress relaxation properties of SC leading to high drying stresses.